Bean breeding in Uganda - Musaana, M.S.; Gridley, Howard E. (International Center for Tropical Agriculture, 1991)
The history of bean breeding in Uganda from 1960-90 is reviewed, covering production constraints, germplasm collections, introductions, and cultivar release. Note is made of the restructuring of the breeding programme in 1989 and the resulting large increase in breeding material handled. Yield results from the 1990b season are presented, showing that breeding lines have been identified with yields over double that of the local cultivar K 20. (AS)